A novel method of studying the core boron transport at ASDEX Upgrade. (26th June 2018) - Bruhn, C; McDermott, R M; Angioni, C; Ameres, J; Bobkov, V; Cavedon, M; Dux, R; Kappatou, A; Lebschy, A; Manas, P; Ochoukov, R
Abstract: A new ion cyclotron resonance frequency (ICRF) modulation technique has been developed and exploited at ASDEX Upgrade for obtaining time perturbed boron density signals. Square wave modulation of the ICRF heating power results in a periodic modulation of the boron density in the edge, which propagates inward. From this time perturbed boron density signal, the boron diffusivity and convection in the radial transport equation are individually determined. This task is done by solving an inverse problem by a quasi-Newton method. This implemented framework has been verified with the Method of Manufactured Solutions and benchmarked with the transport code STRAHL. The experimental transport coefficients are compared with neoclassical calculations with the code NEO and gyrokinetic simulations with the code GKW. The neoclassical diffusivity is well below the experimental one. The comparison to gyrokinetic theory shows a good agreement in the diffusivity, but the theoretical convection predicts a more peaked boron density profile than measured in the experiment.